174k views
1 vote
If it exists, solve for the inverse function of each of the following:

1. f(x) = 25x - 18
6. gala? +84 - 7
7. 10) = (b + 6) (6-2)
3. A(7)=-=-
4. f(x)=x
9. h(c) = V2c +2
+30
10. f(x) =
5. f(a) = a +8
ox-1
2. 9(x) = -1
2x+17
8. () - 2*​

1 Answer

6 votes

Answer:

The solution is too long. So, I included them in the explanation

Explanation:

This question has missing details. However, I've corrected each question before solving them

Required: Determine the inverse

1:


f(x) = 25x - 18

Replace f(x) with y


y = 25x - 18

Swap y & x


x = 25y - 18


x + 18 = 25y - 18 + 18


x + 18 = 25y

Divide through by 25


(x + 18)/(25) = y


y = (x + 18)/(25)

Replace y with f'(x)


f'(x) = (x + 18)/(25)

2.
g(x) = (12x - 1)/(7)

Replace g(x) with y


y = (12x - 1)/(7)

Swap y & x


x = (12y - 1)/(7)


7x = 12y - 1

Add 1 to both sides


7x +1 = 12y - 1 + 1


7x +1 = 12y

Make y the subject


y = (7x + 1)/(12)


g'(x) = (7x + 1)/(12)

3:
h(x) = -(9x)/(4) - (1)/(3)

Replace h(x) with y


y = -(9x)/(4) - (1)/(3)

Swap y & x


x = -(9y)/(4) - (1)/(3)

Add
(1)/(3) to both sides


x + (1)/(3)= -(9y)/(4) - (1)/(3) + (1)/(3)


x + (1)/(3)= -(9y)/(4)

Multiply through by -4


-4(x + (1)/(3))= -4(-(9y)/(4))


-4x - (4)/(3)= 9y

Divide through by 9


(-4x - (4)/(3))/9= y


-4x * (1)/(9) - (4)/(3) * (1)/(9) = y


(-4x)/(9) - (4)/(27)= y


y = (-4x)/(9) - (4)/(27)


h'(x) = (-4x)/(9) - (4)/(27)

4:


f(x) = x^9

Replace f(x) with y


y = x^9

Swap y with x


x = y^9

Take 9th root


x^{(1)/(9)} = y


y = x^{(1)/(9)}

Replace y with f'(x)


f'(x) = x^{(1)/(9)}

5:


f(a) = a^3 + 8

Replace f(a) with y


y = a^3 + 8

Swap a with y


a = y^3 + 8

Subtract 8


a - 8 = y^3 + 8 - 8


a - 8 = y^3

Take cube root


\sqrt[3]{a-8} = y


y = \sqrt[3]{a-8}

Replace y with f'(a)


f'(a) = \sqrt[3]{a-8}

6:


g(a) = a^2 + 8a- 7

Replace g(a) with y


y = a^2 + 8a - 7

Swap positions of y and a


a = y^2 + 8y - 7


y^2 + 8y - 7 - a = 0

Solve using quadratic formula:


y = (-b\±√(b^2 - 4ac))/(2a)


a = 1 ;
b = 8;
c = -7 - a


y = (-b\±√(b^2 - 4ac))/(2a) becomes


y = (-8 \±√(8^2 - 4 * 1 * (-7-a)))/(2 * 1)


y = (-8 \±√(64 + 28 + 4a))/(2 * 1)


y = (-8 \±√(92 + 4a))/(2 * 1)


y = (-8 \±√(92 + 4a))/(2 )

Factorize


y = (-8 \±√(4(23 + a)))/(2 )


y = (-8 \±2√((23 + a)))/(2 )


y = -4 \±√((23 + a))


g'(a) = -4 \±√((23 + a))

7:


f(b) = (b + 6)(b - 2)

Replace f(b) with y


y = (b + 6)(b - 2)

Swap y and b


b = (y + 6)(y - 2)

Open Brackets


b = y^2 + 6y - 2y - 12


b = y^2 + 4y - 12


y^2 + 4y - 12 - b = 0

Solve using quadratic formula:


y = (-b\±√(b^2 - 4ac))/(2a)


a = 1 ;
b = 4;
c = -12 - b


y = (-b\±√(b^2 - 4ac))/(2a) becomes


y = (-4\±√(4^2 - 4 * 1 * (-12-b)))/(2*1)


y = (-4\±√(4^2 - 4 *(-12-b)))/(2)

Factorize:


y = (-4\±√(4(4 - (-12-b))))/(2)


y = (-4\±2√((4 - (-12-b))))/(2)


y = (-4\±2√((4 +12+b)))/(2)


y = (-4\±2√(16+b))/(2)


y = -2\±√(16+b)

Replace y with f'(b)


f'(b) = -2\±√(16+b)

8:


h(x) = (2x+17)/(3x+1)

Replace h(x) with y


y = (2x+17)/(3x+1)

Swap x and y


x = (2y+17)/(3y+1)

Cross Multiply


(3y + 1)x = 2y + 17


3yx + x = 2y + 17

Subtract x from both sides:


3yx + x -x= 2y + 17-x


3yx = 2y + 17-x

Subtract 2y from both sides


3yx-2y =17-x

Factorize:


y(3x-2) =17-x

Make y the subject


y = (17 - x)/(3x - 2)

Replace y with h'(x)


h'(x) = (17 - x)/(3x - 2)

9:


h(c) = √(2c + 2)

Replace h(c) with y


y = √(2c + 2)

Swap positions of y and c


c = √(2y + 2)

Square both sides


c^2 = 2y + 2

Subtract 2 from both sides


c^2 - 2= 2y

Make y the subject


y = (c^2 - 2)/(2)


h'(c) = (c^2 - 2)/(2)

10:


f(x) = (x + 10)/(9x - 1)

Replace f(x) with y


y = (x + 10)/(9x - 1)

Swap positions of x and y


x = (y + 10)/(9y - 1)

Cross Multiply


x(9y - 1) = y + 10


9xy - x = y + 10

Subtract y from both sides


9xy - y - x = y - y+ 10


9xy - y - x = 10

Add x to both sides


9xy - y - x + x= 10 + x


9xy - y = 10 + x

Factorize


y(9x - 1) = 10 + x

Make y the subject


y = (10 + x)/(9x - 1)

Replace y with f'(x)


f'(x) = (10 + x)/(9x -1)

User Danny Brady
by
4.8k points